Metadiscourse Markers in Abstracts of Linguistics and Literature Research Articles from Scopus-Indexed Journals - Geng, Hui; Wei, Han (Journal of Modern Languages, 2023)
An abstract is generally a condensed version of a much lengthier research article (RA). It plays a crucial role in academic writing by initially grabbing the readers’ attention. A well-crafted abstract can greatly increase an RA’s chances of being published. Metadiscourse markers, which extend beyond the actual information being presented, provide significant assistance in textual organisation and interaction. However, less attention has been paid to the use of these markers in the abstracts of RAs within the field of linguistics and literature from Scopus-indexed journals. Therefore, this paper first investigated how authors presented their arguments in the abstracts by deploying interactive and interactional markers, and then it delved into the occurrence frequency of both types of markers in linguistics and literature corpora. A total of 100 English RA abstracts were selected for this study. The linguistics and literature corpus each contained 50 RA abstracts taken from three open-access Scopus-indexed journals. Based on Hyland’s (2005) interpersonal model of metadiscourse, an analysis of the identification and frequency of metadiscourse markers was conducted. A comparison was also drawn between the linguistics and literature RA abstracts. The findings showed that the abstracts from both corpora employed more interactive markers than interactional markers. Regarding the interactive markers, a similar tendency of using transitions was detected. However, the difference lay in the frequency of the other four types of markers between the two corpora. In the interactional category, boosters emerged as the most prominent markers while engagement markers were the least frequent in both corpora. The difference was mainly in the occurrence of self-mentions. The results of this study highlight the disciplinary awareness of metadiscourse markers in RA abstracts and offer a practical guide for scholars to utilise these cues and indicators in academic writing.